Effect of pre-treatments on quality of marian plum (bouea macrophylla) purée - Tran, Thanh Truc; To, Nguyen Phuoc Mai (Journal of Technical Education Science, 2017)
In this study, marian plums at 50 days after anthesis at Vinh Long province were chosen as main ingredient for purée processing. Influence of blanching to inactivating of browning enzyme and the effect of sucrose and pectin additions on purée were studied. The results showed that blanching condition at 80°C in 3 minutes could inactivate browning enzyme, and maintained marian plum’s nutritional values. The cryoprotection effect of added sugar and pectin to purée were noticed. The addition of sucrose to 35°Brix combined with 1.75% pectin have the optimum quality which remained up to 180 days in frozen storage.